A clinical, histopathological, and genetic study of Avellino corneal dystrophy in British families. Issue 7 (1st July 2003) - El-Ashry, M F; El-Aziz, M M Abd; Larkin, D F P; Clarke, B; Cree, I A; Hardcastle, A J; Bhattacharya, S S; Ebenezer, N D
Abstract : Aims: To establish a clinical, histopathological, and genetic diagnosis in two unrelated British families with Avellino corneal dystrophy (ACD). Methods: Genomic DNA was extracted from peripheral blood leucocytes of all members participating in the study. Exons 4 and 12 of the human transforming growth factor β induced ( BIGH3 ) gene were amplified by polymerase chain reaction. The mutation and polymorphism were identified by direct sequencing and restriction digest analysis. A review of the patients' clinical symptoms and signs was undertaken and a histopathological study on corneal specimen obtained from the proband of one family after keratoplasty was performed. Results: A heterozygous G to A transition at the second nucleotide position of codon 124 of BIGH3 gene was detected in all affected members of both families. This mutation changes an arginine residue to a histidine. The clinical diagnosis for ACD was more evident with advancing age. Histopathological study revealed granular deposits in the anterior stroma and occasional positive Congo red areas of amyloid deposition in the mid to deep stroma typical of ACD. Conclusions: This is the first report of ACD families in the United Kingdom and, furthermore, of BIGH3 gene mutation in British patients with this rare type of corneal dystrophy. The results indicate that BIGH3 gene screening along with clinical and histopathological examinations is essential for the diagnosis and clinical management of corneal dystrophies.